2023
DOI: 10.1111/dom.15100
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of remission and relapse of type 2 diabetes mellitus in Japan: Analysis of a nationwide patient registry (JDDM73)

Kazuya Fujihara,
Laymon Khin,
Koshiro Murai
et al.

Abstract: Aims: To determine the incidence of remission and 1-year relapse from remission and associated factors in patients with type 2 diabetes.Materials and methods: A total of 48 320 Japanese patients with type 2 diabetes aged ≥18 years, with glycated haemoglobin (HbA1c) levels ≥48 mmol/mol (6.5%) and/or glucose-lowering drug prescription, were identified from databases of specialist clinics from 1989 and followed until September 2022. Remission was defined as HbA1c <48 mmol/mol at least 3 months after cessation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 47 publications
(110 reference statements)
0
9
0
Order By: Relevance
“…Similarly, in the Delivering the Diabetes Remission Clinical Trial (DiRECT), intervention in early‐stage obese patients with type 2 diabetes was shown to result in the achievement of remission in about half 20 . In our previous study, there was a strong association between body mass index (BMI) reductions over 1 year and remission of diabetes in the analysis of a nationwide patient registry in Japan 6 . Holman et al also reported the same association between body weight reduction and remission in UK, 2 suggesting no ethnic differences in this relationship.…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…Similarly, in the Delivering the Diabetes Remission Clinical Trial (DiRECT), intervention in early‐stage obese patients with type 2 diabetes was shown to result in the achievement of remission in about half 20 . In our previous study, there was a strong association between body mass index (BMI) reductions over 1 year and remission of diabetes in the analysis of a nationwide patient registry in Japan 6 . Holman et al also reported the same association between body weight reduction and remission in UK, 2 suggesting no ethnic differences in this relationship.…”
Section: Introductionmentioning
confidence: 89%
“…In a meta‐analysis of trials of short‐term intensive insulin therapy, two‐thirds of participants achieved remission, but about one‐third relapsed after 12 months 27 . In cohort studies, the same phenomenon was observed 2 and relapse of remission of diabetes occurred in two‐thirds of participants within 1 year 6 . However, few studies have evaluated long‐term remissions in real world settings using consensus definitions for various aspects of diabetes and its remission.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations